2014
DOI: 10.3895/rbgeo.v2n2.5450
|View full text |Cite
|
Sign up to set email alerts
|

O sensoriamento remoto aplicado ao estudo da desertificação na região semiárida do norte de Minas Gerais

Abstract: O fenômeno conhecido como desertificação, resulta da degradação das terras nas zonas áridas, semiáridas e subúmidas secas. É consequência do resultado da pressão antrópica sobre o meio como também das variabilidades climáticas. Os danos ambientais gerados por esse processo afetam de forma direta na qualidade de vida da população, fazendo-se necessário a realização de estudos nessas áreas para que os resultados produzidos sirvam de apoio, seja através de medidas de recuperação ou de prevenção. O objetivo deste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
1
4
0
1
Order By: Relevance
“…Areas identified by Ia (gridded) were also identified by index D (gridded). Regions identified as susceptible to desertification over states of Rio de Janeiro and Minas Gerais coincide with areas already identified in those states in previous studies (Almeida et al 2014;Bohn 2014;Marques et al 2017). A recent study identified areas highly Susceptible to desertification in the state of Rio de Janeiro (Bohn 2014) and emphasized the need for specific public policies for the region.…”
Section: Figuresupporting
confidence: 72%
See 3 more Smart Citations
“…Areas identified by Ia (gridded) were also identified by index D (gridded). Regions identified as susceptible to desertification over states of Rio de Janeiro and Minas Gerais coincide with areas already identified in those states in previous studies (Almeida et al 2014;Bohn 2014;Marques et al 2017). A recent study identified areas highly Susceptible to desertification in the state of Rio de Janeiro (Bohn 2014) and emphasized the need for specific public policies for the region.…”
Section: Figuresupporting
confidence: 72%
“…Based on observed data, areas of dry sub-humid climate, thus susceptible to desertification, were found for stations of group G3 (except Januária, ID 8) and station Campos dos Goytacazes (G1, ID 53). Those stations were located over North Rio de Janeiro and North Minas Gerais, in areas previously identified as susceptible to desertification (Almeida et al 2014). Stations already identified as sub-humid by index D were similarly classified by index Ia.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Diversos estudos têm sido desenvolvidos utilizando esses IV para obtenção de informações biofísicas, tais como nas áreas de desertificação (Almeida et al, 2014 - (Nova et al, 2013 -IVDN); monitoramento de bacia hidrográficas (Martins e Silva, 2014 -NDVI) e outras.…”
Section: íNdices De Vegetaçãounclassified